Consumer Protection Through Information Transparency in Indonesia’s Property Technology System - Maharani Husnul Khotimah Yusri Dewi; Muthia Sakti (Fakultas Syariah INSURI Ponorogo, 2026)
The real estate sector plays a strategic role in Indonesia's economic development, particularly amid the rapid growth of apartment construction. However, this expansion has raised legal issues, particularly regarding the lack of transparency regarding the ownership status and legal validity of the apartment units offered to consumers. This study analyzes the role of Property Technology (PropTech) in ensuring legal certainty and consumer protection within the framework of Law Number 20 of 2011 on Apartment Buildings, Law Number 8 of 1999 on Consumer Protection, and other relevant regulations. The research employs a normative legal method, drawing on statutory, conceptual, and case-based approaches. The analysis is based on primary, secondary, and tertiary legal materials, including legislation, legal doctrines, court decisions, and relevant literature. Unlike existing studies that emphasize the technological and economic dimensions of PropTech, this research investigates its legal implications and capacity to strengthen transparency, legal certainty, and consumer protection in apartment ownership transactions, as data and information provided by developers are digitally documented and may serve as evidence in dispute resolution. In conclusion, PropTech has significant potential to function as a digital instrument that promotes transparency, strengthens legal certainty, and enhances legal protection for apartment consumers in Indonesia.